(untitled) (Annual of the Faculty of Philosophy in Skopje, 2018)
The article explores some of Alcinous’ stances on god from his work ”The Handbook of Platonism”, showing instances of influence by Plato, and of the general philosophical atmosphere of the middle Platonism. Some questions about the concept of Alcinous of the Primary god and the possibilities of anticipation of Plotinus’ One are raised. The attention is directed towards Alcinous’ concept of an ineffable god, graspable only through the intellect, and towards his focus on god’s attributes, or rather on the ways in which some aspects of god are knowable through the abstraction of attributes. The ways of knowing god proposed by Alcinous are the negation or abstraction, analogy, and pre-eminence, and the issue whether these make his approach apophatic will be reviewed in the article, especially through his use of aphairesis (abstraction/negation).